MATHEMATICAL MODELING OF PELVIC MUSCLE FUNCTION IN PATIENTS WITH HIP JOINT ADDUCTION CONTRACTURE AT SINGLE-SUPPORT STANDING - Tyazhelov, Olexiy; Karpinsky, Mykhaylo; Karpinska, Olena; Yurchenko, Denys; Branitsky, Oleksandr (ORTHOPAEDICS TRAUMATOLOGY and PROSTHETICS, 2023)
Long existing hip arthritis is accompanied by the development of pain and contractures that cause contractile muscle spasm, reduction in the length of the adductor muscles and flexors of the thigh, relative overstretching of the abductor muscles, which over time leads to changes in their structure. The result is weakness of the pelvic muscles, the clinical manifestation of which is a violation of postural balance — lameness, torso tilts while walking, changes in pelvic position, etc. Objective. To determine the effect of the hip joint adduction contracture on the ability to maintain balance standing position with mathematical model. Methods: mathematical model is worked out that represents the pelvis with the thigh and the vectors of action of the adductor and abductor muscles. The muscular effort required to maintain body balance during one-leg standing was normal and the hip position was set at 5° and 10°. Calculations were performed for patients weighing 70; 100; 120 kg. Results. It is determined that at the adduction contracture in 5° m. gracilis, m. add magnus, m. piriformis are not able to perform the functions of maintaining body balance due to the necessity to develop greater efforts than their maximum possible, even at the minimal patient’s weight. If the patient’s weight exceeds 120 kg, then almost the entire muscular system of stabilization of the thigh works beyond its capabilities. The adduction contracture of 10° increases the required force of the thigh stabilizer muscles. The absolute values showed an increase in their strength indicators. Conclusions. The adduction contracture of the hip joint causes a change in the biomechanical conditions of the pelvic muscles due to changes in the angles of action of the abductor muscles, reducing the effectiveness of their work to stabilize the pelvis. As the angle of adduction contracture increases, there is a tendency for the pelvic muscles to work effectively. An additional factor that negatively affects this indicator is the patient’s overweight.